MR spectroscopy findings in retired professional Rugby League players - Gardner, A. J.; Iverson, G. L.; Wojtowicz, M.; Levi, C. R.; Kay-Lambkin, F.; Schofield, P. W.; Zafonte, R.; Shultz, S. R.; Lin, A. P.; Stanwell, P. (International Journal of Sports Medicine, 2017)
The aim of this study was to examine brain neurometabolite concentrations in retired rugby league players who had a history of numerous self-reported concussions. Participants were 16 retired professional rugby league players (ages 30-45 years) with an extensive history of concussion and participation in contact sports, and 16 age- and education-matched controls who had no history of neurotrauma or participation in contact sports. All completed a clinical interview, psychological and cognitive testing, and magnetic resonance spectroscopy (MRS) investigation. MRS voxels were placed in posterior cingulate grey matter and parietal white matter. Neurometabolite concentrations were quantified using LCModel. It was hypothesized that retired athletes would differ on N-acetyl aspartate, myo-inositol, choline, glutamate, and glutathione. Retired players had significantly lower concentrations of grey matter glutathione (p=0.02, d=0.91). They did not significantly differ in concentrations of other neurometabolites. There were no significant differences between groups on measures of depression, anxiety, or cognitive functioning. The retired athletes reported significantly greater alcohol use (p<0.01; Cohen`s d=1.49), and they had worse manual dexterity using their non-dominant hand (p=0.03; d=1.08). These preliminary findings suggest that MRS might be modestly sensitive to biochemical differences in athletes after their athletic careers have ended in the absence of clinical differences in cognitive performance and self-reported psychological functioning.